Nanogels as Advanced Topical Drug Delivery Systems: Innovations and Therapeutic Potential - Kaustubhi Chavan; Shilpa Borkar; Jagdish Baheti (Asian Journal of Pharmaceutical Research and Development, 2026)
Nanogels constitute a significant advancement in topical drug delivery systems, effectively addressing critical limitations inherent in conventional formulations such as poor solubility, limited bioavailability, and systemic toxicity. These nanoscale, three-dimensional polymeric networks exhibit distinctive properties including high water content, biocompatibility, and responsiveness to physiological stimuli such as pH, temperature, and enzymatic activity, thereby facilitating controlled and targeted drug release. Nanogels enhance dermal penetration via multiple pathways, improve drug stability, and mitigate local irritation, rendering them particularly suitable for managing dermatological conditions including acne, psoriasis, and atopic dermatitis. Fabrication techniques such as free radical polymerization, ionic gelation, chemical crosslinking, and self-assembly enable the customization of nanogel characteristics to meet specific therapeutic requirements. Despite challenges related to stability, scalability, and production costs, nanogels offer considerable advantages including sustained drug release, targeted delivery, reduced systemic toxicity, and enhanced bioavailability for both hydrophilic and hydrophobic agents. Current review emphasizes the development of smart, stimuli-responsive nanogels and personalized medicine applications, aiming to translate promising preclinical outcomes into clinical practice. Overall, nanogels represent a promising class of next-generation drug carriers, offering safer, more effective, and patient-centric topical therapies.